If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 9(x + -4) = 2 + -5(x + -2) Reorder the terms: 3 + 9(-4 + x) = 2 + -5(x + -2) 3 + (-4 * 9 + x * 9) = 2 + -5(x + -2) 3 + (-36 + 9x) = 2 + -5(x + -2) Combine like terms: 3 + -36 = -33 -33 + 9x = 2 + -5(x + -2) Reorder the terms: -33 + 9x = 2 + -5(-2 + x) -33 + 9x = 2 + (-2 * -5 + x * -5) -33 + 9x = 2 + (10 + -5x) Combine like terms: 2 + 10 = 12 -33 + 9x = 12 + -5x Solving -33 + 9x = 12 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. -33 + 9x + 5x = 12 + -5x + 5x Combine like terms: 9x + 5x = 14x -33 + 14x = 12 + -5x + 5x Combine like terms: -5x + 5x = 0 -33 + 14x = 12 + 0 -33 + 14x = 12 Add '33' to each side of the equation. -33 + 33 + 14x = 12 + 33 Combine like terms: -33 + 33 = 0 0 + 14x = 12 + 33 14x = 12 + 33 Combine like terms: 12 + 33 = 45 14x = 45 Divide each side by '14'. x = 3.214285714 Simplifying x = 3.214285714
| -u+9=u+99 | | x+75=-x+3 | | 5y+22(y-6)=4(y+1)-2 | | P(1000-50P)=0 | | 0=5x^2+4x-3 | | (x+2)(x-3)(x-2)=0 | | 14z=10z-3+3z | | 3x+9+3=19 | | 3x+4(4.5)=18 | | 4x^2+28x-7=0 | | cos*x+cos*2x+cos*3x=0 | | 3+9(x-5)=5-9(x-8) | | (5a+3)(2a-6)=10 | | x+9x=2000000 | | 12x+6=9x+45 | | 8x^3-16x^2=0 | | x*2-3=12 | | 5(12x+5)=60x-4 | | 3x-5=-2b-7 | | 3x+1+9+3x=33 | | 2(5x-3)-3(4x-7)= | | 3x+6+9x+1=36 | | 4n+5=42 | | 4x+3=-24 | | x=y^2-10y+26 | | .2(x-50)+6=0.4(3x+20) | | 6y-4=-11 | | 1-5cos^2x-3cosx=0 | | 3x-12=26 | | -2(4x-3)+x= | | x^2+3ix+5=0 | | 9(2x-3)-3(3x+2)=12 |